Neurons containing orexin or melanin concentrating hormone reciprocally regulate wake and sleep - Konadhode, Roda Rani; Pelluru, Dheeraj; Shiromani, Priyattam J. (Frontiers in Systems Neuroscience, 2015)
There is considerable amount of data on arousal neurons whereas there is a paucity of knowledge regarding neurons that make us fall asleep. Indeed, current network models of sleep-wake regulation list many arousal neuronal populations compared to only one sleep group located in the preoptic area. There are neurons outside the preoptic area that are active during sleep, but they have never been selectively manipulated. Indeed, none of the sleep-active neurons have been selectively stimulated. To close this knowledge gap we used optogenetics to selectively manipulate neurons containing melanin concentrating hormone (MCH). The MCH neurons are located in the posterior hypothalamus intermingled with the orexin arousal neurons. Our data indicated that optogenetic stimulation of MCH neurons in wildtype mice (J Neuroscience, 2013) robustly increased both non-REM and REM sleep. MCH neuron stimulation increased sleep during the animal’s normal active period, which is compelling evidence that stimulation of MCH neurons has a powerful effect in counteracting the strong arousal signal from all of the arousal neurons. The MCH neurons represent the only group of sleep-active neurons that when selectively stimulated induce sleep. From a translational perspective this is potentially useful in sleep disorders, such as insomnia, where sleep needs to be triggered against a strong arousal drive. Our studies indicate that the MCH neurons belong within an overall model of sleep-wake regulation.